2018
DOI: 10.1002/navi.258
|View full text |Cite
|
Sign up to set email alerts
|

Link-Layer Coding for GNSS Navigation Messages

Abstract: In this paper, we face the problem of ensuring reliability of Global Navigation Satellite Systems (GNSSs) in harsh channel conditions, where obstacles and scatter cause long outage events that cannot be counteracted with channel coding only. Our novel approach, stemming from information‐theoretic considerations, is based on link‐layer coding (LLC). LLC allows us to significantly improve the efficiency in terms of time‐to‐first‐fix with respect to current operational GNSSs, which adopt carousel transmission. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…, K} from the ground segment; the choice of π s,n is the true subject of the scheduling discussed in the next Section; 2) satellite s transmits packet π s,n ; 3) each receiver in a position x such that v s,n (x) = 1 decodes the packet; 4) if the receiver has already obtained packet π s,n during previous rounds or from another satellite, it discards the packet, otherwise it stores the packet in its buffer; 5) once the receiver has collected all the K packets, it reconstructs message p and waits for a new message. Note that the proposed protocol is compatible with any channel code mechanism, e.g., the Fountain codes used, for instance, in [1], [9], [14]. Moreover, our solution can also be applied without channel coding.…”
Section: System Modelmentioning
confidence: 94%
See 3 more Smart Citations
“…, K} from the ground segment; the choice of π s,n is the true subject of the scheduling discussed in the next Section; 2) satellite s transmits packet π s,n ; 3) each receiver in a position x such that v s,n (x) = 1 decodes the packet; 4) if the receiver has already obtained packet π s,n during previous rounds or from another satellite, it discards the packet, otherwise it stores the packet in its buffer; 5) once the receiver has collected all the K packets, it reconstructs message p and waits for a new message. Note that the proposed protocol is compatible with any channel code mechanism, e.g., the Fountain codes used, for instance, in [1], [9], [14]. Moreover, our solution can also be applied without channel coding.…”
Section: System Modelmentioning
confidence: 94%
“…Algorithm 2 is the proposed strategy for the Maximization of the Average Number of Different Received Packets (MRP), where marp_max solves (1) and round_eval is a function that takes as input the set of received packets at the end of the previous round, u k,n−1 (P n−1 , x), and outputs the coverage and the set of received packets at the end of round n, u k,n ({P n−1 , S n }, x), by using ( 2)- (9).…”
Section: B Maximization Of the Average Number Of Different Received P...mentioning
confidence: 99%
See 2 more Smart Citations
“…They introduced several coding methods used in present-day GNSS signals, and then their performance against noise and interference was evaluated based on block error rate. Tarable et al (2018) explored the appropriateness of link layer coding techniques for Galileo I/ NAV messages (Tarable et al, 2018). They found that the use of simple link-layer codes offers a substantial reduction in signal processing time.…”
Section: Introductionmentioning
confidence: 99%